1991
DOI: 10.1577/1548-8667(1991)003<0176:mabiad>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal-Antibody-Based Immunodot Assay Distinguishes between Viral Hemorrhagic Septicemia Virus (VHSV) and Infectious Hematopoietic Necrosis Virus (IHNV)

Abstract: An immunodot assay has been developed with two monoclonal antibodies that recognize conserved epitopes on the nucleoproteins of viral hemorrhagic septicemia virus (VHSV) and infectious hematopoietic necrosis virus (IHNV). Monoclonal antibody 1NDW14D, which recognizes a conserved epitope on the nucleoprotein of IHNV, recognized 80 of 81 IHNV isolates spotted on nitrocellulose, but none of 8 VHSV isolates. Monoclonal antibody IP5B11, which recognizes a conserved epitope on the nucleoprotein of VHSV, reacted with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Nonspecific binding sites were blocked for lh with 5% non-fat powdered milk (Saco Foods, Madison, WI, USA) in PBS. Blocking solution was blotted off and sections were incubated for lh with a anti-nucleocapsid monoclonal antibody (1NDW14D) whieh is specific for a highly conserved region of the nucleoeapsid protein, and has been shown by direct immunofluorescence and immunoblotting to recognize all five IHNV types (Ristow & Arnzen 1989;Ristow, Lorenzen & Vestergaard J0rgensen 1991). Slides were then incubated for 30min with biotinylated goat anti-mouse polyelonal antibody, followed by a lh incubation with phosphatase-conjugated avidin-biotin complex (Vectastain-ABC mouse IgG kit, Vector Laboratories, Burlingame, CA, USA).…”
Section: Alkaline Phosphatase Immunohistochemistry (Apih)mentioning
confidence: 99%
“…Nonspecific binding sites were blocked for lh with 5% non-fat powdered milk (Saco Foods, Madison, WI, USA) in PBS. Blocking solution was blotted off and sections were incubated for lh with a anti-nucleocapsid monoclonal antibody (1NDW14D) whieh is specific for a highly conserved region of the nucleoeapsid protein, and has been shown by direct immunofluorescence and immunoblotting to recognize all five IHNV types (Ristow & Arnzen 1989;Ristow, Lorenzen & Vestergaard J0rgensen 1991). Slides were then incubated for 30min with biotinylated goat anti-mouse polyelonal antibody, followed by a lh incubation with phosphatase-conjugated avidin-biotin complex (Vectastain-ABC mouse IgG kit, Vector Laboratories, Burlingame, CA, USA).…”
Section: Alkaline Phosphatase Immunohistochemistry (Apih)mentioning
confidence: 99%
“…We demonstrated by Western blotting that the nucleocapsid monoclonal antibody binding was specific to VHSV versus SVCV, another rhabdovirus that is present in Wisconsin. Previous studies showed a lack of cross-reaction between the antibody used herein and spring viremia of carp virus, infectious hematopoietic necrosis virus, pike fry rhabdovirus, or rhabdovirus anguilla (26,56). According to the manufacturer of the antibody (Aquatic Diagnostics, Stirling, Scotland), no cross-reaction of the antibody occurs with nodavirus, infectious salmon anemia virus, koi herpesvirus, salmon alphavirus (1, 2, and 3), or Piscirickettsia salmonis infected cells.…”
Section: Discussionmentioning
confidence: 89%
“…Most probably, broad antigenic variations exist regarding virion configuration (Luo et al, 1990;Ristow, 1991), therefore neutralisation mechanisms have not been clarified yet. Interestingly, MAb 2E1 did not react in Western blotting even after separation with non-reducing conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The ELISA method can only demonstrate the presence of viral immunogenic particles, and not infectivity of the virus, therefore, no significant correlation was attributed to infectious titre of particular isolates and the ELISA test, due to differences existing in relative amounts of incomplete or decomposed viral particles (Ristow, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation